The Impact of Sponsorship and Customer Engagement on Brand Awareness: The Mediating Role of Brand Image - Ayu Syispratiwi; Prasetyo Hadi; Maria Assumpta Wikantari (Ilomata International Journal of Social Science, 2026)
Intensifying competition in the food and beverage industry has heightened the strategic relevance of sponsorship activities and customer engagement in shaping consumer-based brand outcomes. This study examines the statistical associations between sponsorship programs, customer engagement, and brand awareness, with brand image positioned as an intervening construct, within the specific context of PT Wingsfood’s Mie Sedaap product sampling program in Mampang. Employing a quantitative research design, the study utilized purposive sampling to collect data from N = 280 respondents who had participated in the sampling program. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a bootstrapping procedure to assess the significance of the hypothesized relationships. The findings reveal that sponsorship and customer engagement are statistically associated with brand awareness, both directly and indirectly through brand image as a mediating variable. These results underscore the importance of integrating experiential marketing initiatives with interactive consumer engagement strategies to strengthen brand positioning in highly competitive markets.